Eleventh European Powder Diffraction Conference : Warsaw, September 19-22, 2008 (De Gruyter Oldenbourg, 2009)
Zeitschrift für Kristallographie. Supplement Volume 30 presents the complete Proceedings of all contributions to the XI European Powder Diffraction Conference in Warsaw 2008: Method Development and Application Instrumental Software Development Materials Supplement Series of Zeitschrift für Kristallographie publishes Proceedings and Abstracts of international conferences on the interdisciplinary field of crystallography.